NEGATIVE THERMAL ION MASS SPECTROMETRY OF OXYGEN IN PHOSPHATES - Holmden C.; Papanastassiou D.A.; Wasserburg G.J. (My University, 1997)
A novel technique for the precise measurement of oxygen isotopes by negative thermal ion mass spectrometry (NTIMS) is presented. The technique is ideally suited to the analysis of oxygen isotopes in phosphates which form intense PO-3 ion beams. Since P is monoisotopic, the mass spectrum for PO-3 at 79, 80, and 81 corresponds to 16O, 17O, and 18O. Natural and synthetic phosphates are converted and loaded on the mass spectrometer filament as Ag3PO4 precipitated directly from ammoniacal solution. To lower the work function of the filament, BaCl2 is added in a 1:1 molar ratio of PO4:Ba. Using these procedures, Br- mass interference (at 79 and 81 amu) is eliminated for typical analyses. Experiments with 18O-enriched water show less than 1% O-exchange between sample PO4 and adsorbed water, and there is no O-exchange with trace O2 present in the mass spectrometer source chamber. The ionization efficiency of PO4 as PO-3 is >10% compared to 0.01% for both conventional dual inlet Gas Isotope Ratio Mass Spectrometry (GIRMS) and secondary ion mass spectrometry (SIMS). Therefore, NTIMS offers exceptional sensitivity enabling routine and precise oxygen isotope analysis of submicrogram samples of PO4 (<21 nmoles equivalent co2 gas) without need for lengthy chemical pretreatment of the sample. Overall external precision is +/-1%% (2σ) for 18O/16O and 17O/16O with reproducibility of instrumental isotope fractionation (calculated from 18O/16O) of +/-0.5%% amu-1. Small phosphate samples including single mineral grains from meteorites, or apatite microfossils, can be analyzed by this technique.